Auto Coloring with Enhanced Character Registration. (22nd November 2007) - Qiu, Jie; Seah, Hock Soon; Tian, Feng; Chen, Quan; Wu, Zhongke; Melikhov, Konstantin
Abstract : An enhanced character registration method is proposed in this paper to assist the auto coloring for 2D animation characters. After skeletons are extracted, the skeleton of the character in a target frame is relocated based on a stable branch in a reference frame. Subsequently the characters among a sequence are automatically matched and registered. Occlusion are then detected and located in certain components segmented from the character. Two different approaches are applied to color regions in components without and with occlusion respectively. The approach has been tested for coloring a practical animation sequence and achieved high coloring accuracy, showing its applicability in commercial animation production.